Perturbation-based dual task assessment in older adults with mild cognitive impairment - Kannan, Lakshmi; Pitts, Jessica; Szturm, Tony; Purohit, Rudri; Bhatt, Tanvi (Frontiers in Rehabilitation Sciences, 2024)
Background: Dual tasking (i.e., concurrent performance of motor and cognitive task) is significantly impaired in older adults with mild cognitive impairment (OAwMCI) compared to cognitively intact older adults (CIOA) and has been associated with increased fall risk. Dual task studies have primarily examined volitionally driven events, and the effects of mild cognitive impairment on reactive balance control (i.e., the ability to recover from unexpected balance threats) are unexplored. We examined the effect of cognitive tasks on reactive balance control in OAwMCI compared to CIOA. Methods: Adults >55 years were included and completed the Montreal Cognitive Assessment (MoCA) to categorize them as OAwMCI (MoCA: 18-24, n=15) or CIOA (MoCA: ≥25, n=15). Both OAwMCI (MoCA: 22.4(2.2), 65.4(6.1) years, 3 females) and CIOA (MoCA: 28.4(1.3), 68.2(5.5) years, 10 females) responded to large magnitude stance slip-like perturbations alone (single task) and while performing perceptual cognitive tasks targeting the visuomotor domain (target and tracking game). In these tasks, participants rotated their head horizontally to control a motion mouse and catch a falling target (target game) or track a moving object (track). Margin of stability (MOS) and fall outcome (harness load cell >30% body weight) were used to quantify reactive balance control. Cognitive performance was determined using performance error (target) and sum of errors (tracking). A 3x2 repeated measures ANOVA examined the effect of group and task on MOS, and generalized estimating equations (GEE) model was used to determine changes in fall outcome between groups and tasks. 2x2 repeated measures ANOVAs examined the effect of group and task on cognitive performance. Results: Compared to CIOA, OAwMCI exhibited significantly deteriorated MOS and greater number of falls during both single task and dual task (p<0.05), and lower dual task tracking performance (p<0.01). Compared to single task, both OAwMCI and CIOA exhibited significantly deteriorated perceptual cognitive performance during dual task (p<0.05); however, no change in MOS or fall outcome between single task and dual task was observed. Conclusion: Cognitive impairment may diminish the ability to compensate and provide attentional resources demanded by sensory systems to integrate perturbation specific information, resulting in deteriorated ability to recover balance control among OAwMCI.